Estimating the transition time from school to university using a stochastic mortality model - Britta Stöver (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2019)
The sufficient provision of university places is of high sociopolitical importance as it facilitates the participation in higher education as well as the accumulation of human capital both being important factors for wealth and economic growth. The aim of this paper is to use the concept of mortality rates for forecasting the transition from school graduates into university in order to enrich and enhance the planning of the needed university places for first-year students. The transition rates differentiated in 16 Federal States and two types of university entrance qualifications were interpreted as mortality rates, fitted with the classical Lee-Carter approach and forecasted with automatically selected ARIMA processes. The results suggest that the constancy assumption used for the original planning provides indeed the best approach for many Federal States. Nevertheless, the application of the well-established Lee-Carter mortality model offers the opportunity to estimate an alternative number of first-year students and to open up a range of possible solutions.
Keywords: C22; I21; I23; J11; 330; Mortality rates; mortality model; transition rates; university enrolment; first-year students